DIGITAL TECHNOLOGIES, DATA, AND ANALYTICS: Automated Hovering for Lower Extremity Joint Replacement Surgery (HomeConnect+): A Randomized Clinical Trial. (20th August 2020) - Mehta, S.; Hume, E.; Troxel, A.; Reitz, C.; Norton, L.; Lacko, H.; McDonald, C.; Freeman, J.; Marcus, N.; Volpp, K.; Asch, D.
Abstract : Lower extremity joint replacement (LEJR) is the most common inpatient surgery for Medicare beneficiaries with substantial variation in cost and quality. Remote monitoring and insights from behavioral science have the potential to improve outcomes and value of care. We evaluated the impact of activity monitoring and bidirectional text messaging on the rate of patient discharge to home and clinical outcomes. This was a three‐arm pragmatic randomized controlled trial conducted between February 2018 and April 2019 at two urban hospitals in a large academic health system (clinicaltrials.gov NCT0335549). Eligible patients were randomized evenly, with a waiver of informed consent, and stratified by hospital location and joint type (knee or hip) to receive (1) usual care, or (2) HomeConnect + . Intervention patients were invited to participate in HomeConnect+ by mailed invitation followed by up to 4 phone calls. Those who agreed received a wearable activity monitor (Withings) to track step counts, pain score tracking, messaging about post‐operative goals and milestones, and connection to clinicians as needed. Those in HomeConnect+ were further randomized evenly to (2a) remote monitoring alone or (2b) remote monitoring with gamification and social support. HomeConnect+ was offered before surgery, began at hospital discharge, and continued for 45 days post‐discharge. The primary outcome was discharge to home. Pre‐specified secondary outcomes included change in average daily step count from week 2 to week 6, rehospitalizations, and outpatient visits. We included patients aged 18‐85 scheduled to undergo lower extremity joint replacement surgery (knee or hip) with a Risk Assessment and Prediction Tool score of 6‐8. We excluded patients with dementia, end‐stage renal disease, cirrhosis, metastatic cancer, and those scheduled for bilateral or revision surgery. A total of 242 patients were included in the analysis (124 usual care, 118 intervention) with a mean age of 66, including 78% female, 46% white, and 43% black patients. 81% in the intervention arm agreed to receive monitoring. There was no significant difference in the rate of discharge to home between the usual care (58%) and intervention (57%) arms; no difference in office visits between arms; and no significant increase in step count in those receiving remote monitoring plus gamification and social support compared to remote monitoring alone. There was a statistically significant reduction in rehospitalization rate in the intervention arm compared to the usual care arm (3.4% vs 12.2%; P = .01). The HomeConnect+ automated hovering program did not increase discharge to home from the hospital after LEJR surgery, and there was no difference in activity levels among those receiving gamification and social support compared to remote monitoring alone. However, there was a significant reduction in rehospitalizations among those receiving the intervention, which may have resulted from goal setting and connection to the care team. Automated hovering was not sufficient to increase discharge to home among patients with a moderate expected rate of facility placement. However, it has the potential to reduce hospitalizations after LEJR surgery, an important quality and value outcome for hospitals and payers.